A phylogenetic approach to study the origin and evolution of plasmodesmata-localized glycosyl hydrolases family 17 - Gaudioso-Pedraza, Rocio; Benitez-Alfonso, Yoselin (Frontiers in Plant Science, 2014)
Colonization of the land by plants required major modifications in cellular structural composition and metabolism. Intercellular communication through plasmodesmata (PD) plays a critical role in the coordination of growth and cell activities. Changes in the form, regulation or function of these channels are likely linked to plant adaptation to the terrestrial environments. Constriction of PD aperture by deposition of callose is the best-studied mechanism in PD regulation. Glycosyl hydrolases family 17 (GHL17) are callose degrading enzymes. In Arabidopsis this is a large protein family, few of which have been PD-localized. The objective here is to identify correlations between evolution of this protein family and their role at PD and to use this information as a tool to predict the localization of candidates isolated in a proteomic screen. With this aim, we studied phylogenetic relationship between Arabidopsis GHL17 sequences and those isolated from fungi, green algae, mosses and monocot representatives. Three distinct phylogenetic clades were identified. Clade alpha contained only embryophytes sequences suggesting that this subgroup appeared during land colonization in organisms with functional PD. Accordingly, all PD-associated GHL17 proteins identified so far in Arabidopsis thaliana and Populus are grouped in this ‘embryophytes only’ phylogenetic clade. Next, we tested the use of this knowledge to discriminate between candidates isolated in the PD proteome. Transient and stable expression of GFP protein fusions confirmed PD localization for candidates contained in clade alpha but not for candidates contained in clade beta. Our results suggest that GHL17 membrane proteins contained in the alpha clade evolved and expanded during land colonization to play new roles, among others, in PD regulation.